Bibliometrics and alternative metrics: Contributions of scientific production in Scopus Elsevier (1999-2020) for public policies on youth - Gómez Brenes, Carmen (2023)
Objective: To analyze the theoretical and methodological contributions of the scientific production registered in Scopus Elsevier, corresponding to the period 1999-2020, about youth, intergenerational and intragenerational relations for the formulation, implementation and evaluation of public policy. Methodology. Traditional bibliographic and alternative metrics were used following this steps: 1. Identification of key words on the subject of youth and public policies, 2. Definition of the research formula, 3. Generation of a database with scientific articles on the subject of interest, 4. Document review and information analysis, 5. Evaluation of traditional and alternative metrics. Results. 5 of 74 scientific articles identified on the subject of youth and inter and intragenerational relations were used in policy documents in Switzerland, Australia, the United States of America and the United Kingdom. Conclusions. The scientific articles found are oriented to the use of the participatory approach that recognizes the relevance of the participation, voice and involvement of girls, boys and young people for the creation of relational knowledge that contemplates intergenerationality and intersectionality.